Penanganan Semen Beku Pasca Distribusi dari Depo Provinsi dan Hubungannya Terhadap Kualitas Semen Beku di Sumatera Barat: Handling of Frozen Semen and Its Correlation on Quality of Frozen Semen in West Sumatra - Nilna; Hendri; Asdi Agustar (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2026)
The objective of this study was to obtain information related to the handling of frozen semen by officers at frozen semen depots in districts/cities and inseminators in West Sumatra and to determine its relationship to frozen semen quality in West Sumatra Province. The study was conducted in 11 districts/cities in West Sumatra. The objects of this study were officers and frozen semen at depot locations and AI stations in the study area. The observed variables include the distribution and handling of frozen semen by officers at depots and AI stations and the quality of frozen semen with the variables motility, viability and abnormality of sperm. The semen quality data were analyzed using simple regression analysis, while frozen semen handling data were analyzed using descriptive analysis. The finding of this study indicated a significant decline in semen motility and viability (P<0.05) from provincial depots to district/city depots. However no statistically significant correlation was observed between sperm abnormalities at depot locations and semen motility, viability and abnormalities at AI stations (P>0,05). The study  revealed that three districts/cities and one AI station exhibited substandard, semen distribution practices, classified as "sufficient." category. The factors contributing to this decline include supporting facilities, frozen semen transportation, and trained personnel.  These factors are suspected to be the primary causes of the significant deterioration in semen quality from provincial depots to district/city depots.